Diamond-like carbon coatings in endoprosthetics (literature review) - Makarov, Vasyl; Strel’nitskij, Vladimir; Dedukh, Ninel; Nikolchenko, Olga (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2019)
Based on literature data, the results of experimental studies and clinical application of diamond-like carbon (DLC) films as coatings of the endoprosthesis metal components are estimated. Most implants used in orthopedics and traumatology are made of various metals and their alloys. Being a long time in the human body, they exhibit certain cytotoxicity as a result of corrosion and migration of particles or metal ions. DLC coatings are considered as a promising material for use in orthopedic implants due to the unique combination of properties such as biocompatibility, hardness, chemical inertness, high wear resistance, corrosion resistance and electrical resistance, and low friction coefficient. In vitro studies has found that the surface of DLC coatings creates favorable conditions for the adhesion and growth of various cells in cultures, including fibroblasts, osteoblasts, macrophages, does not cause cytotoxicity and inflammatory reaction. The results of testing DLC films in vivo indicate their biocompatibility and the absence of inflammatory reactions in the animal’s body. The results of tribological studies concerning the influence of DLC on the wear of the friction pairs of orthopedic implants were controversial. Some studies have found that these coatings in the simulators of the hip and knee joints reduce to a minimum the wear, corrosion and release of metal ions from the metal base of implants. In this case, DLC coatings show a wide range of changes in the structure and properties of coatings, depending on the conditions of their application, which determines the ratio of atomic diamond sp3- and graphite sp2-bonds. Due to the high residual internal compressive stress, DLC exhibit a tendency to arbitrarily crack and flake, which can lead to the wear of the working surfaces of the friction pair and is a major problem for the widespread introduction of these coatings into orthopedic practice, since friction pairs working under heavy load conditions. One of the ways to solve this problem is to improve the technologies of their application on the basis and reduce the compressive stress in the synthesized coatings.